A Generalization of the Transportation Problem in Linear Programming and Spatial Price Equilibrium - John M. Hartwick (Queen's University, Department of Economics, 1970)
The Hitchcock-Koopmans (HK) transportation problem in linear programming (4), (5) and the Cournot-Enke-Samuelson (KES) pricing problem in spatial price equilibrium (2), (3), (6) are two classic analyses in the theory of transportation costs. In this paper, I generalize the HK analysis to take account of variable supplies and demand for a product at the diverse geographically separated locations.
Keywords: 330